Towards improving the healthcare services in least developed countries: A case of health needs assessment for telehealth in Yemen - Al-Fadhli A.A.; Othman M.; Ali N.; Al-Jamrh B.A. (Springer Science and Business Media Deutschland GmbH, 2023)
eHealth; Medical computing; Public health; Rural areas; Health facilities; Health information systems; Health informations; Health professionals; Health-care system; Healthcare services; Least-developed countries; Qualitative approach; Distributed database systems